Proyecto de exportacion de piña colombiana a cesena, Italia (2021)
This project was born from the moment that the business opportunity is identified in the form of a project carried out by the Antonio Nariño University in 2020, This project consists of the start-up of an intermediary company between the Colombian companies that produce pineapple and the companies pineapple importers in Cesena Italy, based on the diversity of natural resources of different types of quality that Colombia offers, which makes other countries interested in importing their products. The department of Tolima is located in the central-western zone of the country of Colombia, regarding the production of pineapple this is among the 10 pineapple producers in the country, and due to its location, it allows easy collection of MD2 pineapple by from different suppliers. This fruit is chosen by this project for export to Cesena Italy as it meets the quality and a series of export-type characteristics that adapt to the requirements established by the European Union.